Perancangan Aplikasi Sistem Informasi Gelanggang Olahraga Berbasis Web Menggunakan Framework Laravel - David Setia Darmawan; Eko Sediyono (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The Youth and Sports Office of Salatiga City has the task of assisting the Mayor in carrying out government affairs which are the authority of the Region in the field of youth and sports as well as the formation tasks assigned to the region. The Salatiga City Youth and Sports Office has a sports arena that can be used by the community, especially the Salatiga city community. Unfortunately, the Salatiga City Youth and Sports Office still doesn't have the media for ordering sports arenas online. The purpose of this research is to design a web-based sports arena information system application using the Laravel framework. The result of designing this application is a sports arena information system website that can make it easier for the people of Salatiga City and immigrants from outside the city of Salatiga to order sports arenas online without having to leave the house first.